Pencegahan dan Penanganan Perilaku Agresif Remaja Melalui Pengelolaan Amarah (Anger Management) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study examined the effectivity of the anger management program for reducing aggression in risk's adolescents. Through the cognitive-behavioral approach, the program was designed to process the cognitive, affective, and behavior aspects together for managing anger and facing the provocative situation without aggression. Fourteen participants in experimental group following eigth sessions of anger management program in 4 weeks, and 14 participants in control group do not obtain any treatment. The measurement of aggression to be held before the' program start and a week after the program end. With the Anava Mixed Design, the result show that the anger management program have a significant effect in the changes of the participant's aggression [F(1,22)=6.300, p